THE INFLUENCE BETWEEN STUDENTS’ LANGUAGE POTENTIAL WITH THEIR OWN DIALECT - Surya Adi Kusumah; Silpia Rahayu (PROJECT (Professional Journal of English Education), 2020)
This study was conducted to obtain information about dialect in student's potential whether it could be decided to speak fluently or not. Taken from one of institute which appear the idea to analyze the problem, the main instrument to collect the data was questionnaire and transform it to be narrative which aimed this research use qualitative method. From 4 dialects were used by the students namely Bataknese, Minangnese, Javanese and Sundanese which they use when speaking, especially the dialect’s intonation usage within English speaking. This will be impact on the learning method that might be constant rather than variable within English intonation usage. The questionnaire result will prove about the problem that occur in amid of the classroom. Moreover, this research has been supported from more than 10 theories instead. It contains many different topics related dialect and student's potential in speaking. From finding, the researcher obtained the data that talking with person who have strong dialect was not such a big problem to understand what does the person mean. The result is not change the dialect the person used, the only thing is practice English intonation to be better and develop the person's language potential to adjust the language the person speaks. Keywords:         Dialect, English intonation, Student’s Potential